2005
DOI: 10.5694/j.1326-5377.2005.tb06643.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of venous thromboembolism after hip and knee replacement surgery

Abstract: Objective: To determine the prevalence of venous thromboembolism (VTE) after total hip replacement (THR), total knee replacement (TKR) or bilateral TKR in a large sample of patients in a major hospital orthopaedic unit. Design, setting and patients: The Mater Misericordiae Hospital, North Sydney, NSW, a 195‐bed private hospital. All patients who had THR, TKR or bilateral TKR at the hospital between 1 April 1995 and 31 December 2001 had physical prophylaxis (graduated compression elastic stockings or intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 23 publications
1
27
1
3
Order By: Relevance
“…Pooled analysis of data from the Regulation of Coagulation in Orthopaedic Surgery to Prevent Deep Vein Thrombosis and Pulmonary Embolism (RECORD) trials revealed a 0.85% incidence of symptomatic VTE following THA and TKA. When patients routinely undergo venography or ultrasonography post‐operatively, incidence figures for VTE are significantly higher than our findings and other reported rates of symptomatic VTE . This likely includes thromboses that may otherwise have not become apparent clinically.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Pooled analysis of data from the Regulation of Coagulation in Orthopaedic Surgery to Prevent Deep Vein Thrombosis and Pulmonary Embolism (RECORD) trials revealed a 0.85% incidence of symptomatic VTE following THA and TKA. When patients routinely undergo venography or ultrasonography post‐operatively, incidence figures for VTE are significantly higher than our findings and other reported rates of symptomatic VTE . This likely includes thromboses that may otherwise have not become apparent clinically.…”
Section: Discussioncontrasting
confidence: 73%
“…When patients routinely undergo venography or ultrasonography post-operatively, incidence figures for VTE are significantly higher than our findings and other reported rates of symptomatic VTE. [32][33][34][35][36] This likely includes thromboses that may otherwise have not become apparent clinically. It is likely that several of the thromboses included in our figures were detected through screening ultrasonography prior to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in bleeding outcomes were not detected between the two agents. VTE outcomes were much lower in this trial, secondary to the inherent lower VTE frequency following THA . Although similarities exist between the ADVANCE trials and our study, differences in the timing of administration of thromboprophylaxis limits the validity of a direct comparison.…”
Section: Discussionmentioning
confidence: 90%
“…This was despite chemical and physical thromboprohylaxis. 13 The rate of equivalent asymptomatic deep vein thrombosis after shoulder arthroplasty was found to be about 13% in one prospective study. 14 The rate of symptomatic deep vein thrombosis is much lower, however.…”
Section: Venous Thromboembolismmentioning
confidence: 99%